A Review: Is Ginger (Zingiber officinale var. Roscoe) Potential for Future Phytomedicine? - Dina Mulyana Syafitri; Jutti Levita; Mutakin Mutakin; Ajeng Diantini (Indonesian Journal of Applied Sciences, 2018)
AbstractZingiber officinale Roscoe (red:ginger), is one of the most widely consumed medicinal herbs in the world has been widely used to treat various disorders in Indonesia. There are three known types of ginger: giant ginger or white ginger (Zingiber officinale var. Roscoe), small white ginger or ginger emprit (Zingiber officinale var. Amarum), and red ginger (Zingiber officinale var. Rubrum). The main components of ginger rhizome are carbohydrates, lipids, essential oils, terpenes, and phenol compounds such as gingerol (23-25%) and shogaol (18-25%). Many studies had confirmed benefical effects of ginger against inflammation, free radicals, diabetes melitus, bacterial infection, cancer, nausea, etc. Z. officinale var. rubrum is considered a safe herbal remedy with only slight and not significant adverse effects. This plant is potential fur future phytomedicine, however it needs further explorations on its clinical studies in humans is expected, especially the efficacy and safety of the risk of side effects.